If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-6(x+7)=-5+2(x-5)
We simplify the equation to the form, which is simple to understand
5x-6(x+7)=-5+2(x-5)
Reorder the terms in parentheses
5x+(-6x-42)=-5+2*(x-5)
Remove unnecessary parentheses
+5x-6x-42=-5+2+*(+x-5+)
Reorder the terms in parentheses
5x-6x-42=-5+(+2x-10)
Remove unnecessary parentheses
+5x-6x-42=-5+2x-10
We move all terms containing x to the left and all other terms to the right.
+5x-6x-2x=-5-10+42
We simplify left and right side of the equation.
-3x=+27
We divide both sides of the equation by -3 to get x.
x=-9
| 4x+16y=32 | | 2.4h=-8.4 | | 2x+4y=30.5 | | 7a+4a= | | 9(x-3)=5+8x | | 4(-x-8)=7(3+7x) | | 1-5x^2=4x^2+12x | | 4z-7=5z-4 | | 3x^4-10x^2-8=0 | | 5m-8-3m=-12 | | a+2(7b+5+9a)-5b= | | 3(30)+x(9)=y(5) | | 2x+4y=3.05 | | 8/-5+3=-13 | | 8*(4.5+x)+8x=372 | | 800983838443+3728732987382= | | 3(-u-5)+8(2u+1)=0 | | 7r-5-6=4(r+1)+3(2r+1) | | 6x-8=8x-3x | | 9(x+18)+12=8(x+8)+10 | | 2x+1=2x+3 | | 2d+10=6-10 | | 3x+3(2x-1)=4x+-7 | | -4(3u-1)+7(3-2u)=0 | | -6(x+4)=-6(x+1) | | x^2+5-36=0 | | 3d+d-7=6.3 | | -4x-5(-x+10)=-43 | | 4x+7-3(x-4)=-26 | | 2x+136-136=180-136 | | x-0.2x=0 | | 4x+3x=6x+9 |